Maintenance and fertility restoration of CMS system in sweet pepper (Capsicum annuum) - SWAMY, B N; SHARMA, V K; ARPITA, S; KUMAR, RAJ; KUMAR, RAJ; BEHERA, T K; MANISHA, M; CHANDRESH, C; MUKESH, K (The Indian Journal of Agricultural Sciences, 2019)
CMS based breeding is essentially a 3-line hybridization method which requires stable CMS line, maintainer line and restorer of fertility line. To identify maintainer (B) and restorer of fertility (R) lines for five stable CMS lines in capsicum, the present experiment was conducted in line × tester mating design at ICAR-IARI, Regional Station, Katrain (HP), India during summer season of 2015 and 2016. The results revealed that among 125 F1s, pollen fertility percent, pollen germination percent, self fruit setting rate and seed number per fruit in C1 × P1, C2 × P2, C2 × P12, C3 ×P3, C3 × P12, C4 × P4, C4 × P12 and C5 × P5 were recorded nil. It revealed that testers in these crosses could be maintainer line (N rfrf) for maintaining sterility in their maternal parent in the cross, whereas in C1 × P6, P15, P10, P9, P14, P8, P7; C2 × P8, P14, P15, P9, P10, P13, P7; C3 × P7, P9, P10; C4 × P23, P24, P7, P21, P6, P9, P10 and C5 × P21, P9, P10 crosses pollen fertility percent were recorded in range of 80.3 to 91.3 and pollen germination per cent were in range of 80.2 to 93.8 and these results indicated that nucleus of pollen parent in these crosses must have dominant Rf allele in homozygous/ heterozygous state and could be exploited as R- line (S/N RfRf / Rfrf) in specific CMS genotype. Our findings would be useful for developing new CMS and R-lines in sweet pepper (Capsicum annuum L. var. grossum).